Collective Security under the Gulf Cooperation Council: problems and prospects (Journal of Oriental Studies, 2018)
The Gulf Cooperation Council (GCC) is the short and more popular name of the organization of theCooperation Council for the Arab States of the Gulf, which is most often found in the Arabic-languageand English-language scientific literature. In this article, the author examines the main problems of thedevelopment of the GCC organization at the present stage, including the attempts of the participatingcountries to create an effective system of collective security. Despite the fact that more than thirty yearshave passed since the creation of the organization, but so far the GCC countries have not been able tofully integrate to ensure regional security. In this regard, the flagship of the intra-Arab integration processes,Saudi Arabia sees an outlet in broad political integration. However, the horizons of such integrationare difficult to predict. On the one hand, at the time of the establishment of the organization, theissue of political integration was not fixed in the Charter of the Council. And, apparently, this was donedeliberately taking into account the complex processes of the formation of regional states. But on theother hand, the issue of political integration of such close countries seemed inevitable, and only the timeand political will of the elites are needed for this. Therefore, when at the end of 2011 the King of SaudiArabia proposed the creation of the Gulf Union on the basis of the GCC, it seemed that this initiative would be the impetus for the organization to reach a new level. But the subsequent policies of someparticipating countries and the flaring “Qatari crisis” in 2017 clearly demonstrated the systemic natureof the problems in this organization, which hinder political integration. The methodology of the researchis based on a comparative historical analysis, both the main political and military events, and the realpolicy of states (realpolitic).